INFRASTRUKTURA A WZROST I ROZWÓJ GOSPODARCZY - Ratajczak, Marek (Wydział Prawa i Administracji UAM, 2000)
The main threads of the debate on importance of infrastructure as a condition for growth and development processes have been, presented in the article - starting from the idea of the so-called „big push” and ending with the theory o f endogeneous growth. Especially the last mentioned conception seems to be of particular importance not only from the point of view of originality of viewing mechanisms o f economic growth but also in what concerns some essential implications for economic politics. Taking into consideration different conceptions we must state that there is no doubts at all that an infrastructure is necessarily needed for the processes of growth and development could ever take place. It does not however mean that it is possible to consider the infrastructure and adequate public financial allocations as being a factor sufficient for to initiate and then maintain growth processes or even a factor guaranteeing increased activity of private sector. Also it is not possible to univocally determine the direction of casualness in the relationship between economic growth and infrastructure. An interdependence occurs in this case, however it could be very hard to treat univocally one o f the variables as being independent. A lack of simple casualness between the infrastructure and economic growth can not nevertheless be identified with marginal character o f the meaning of changes in infrastructure for the results of economic activity. A long lasting infrastructural indigence and consequently - poor services rendered - do weaken or even in extreme situation can render it impossible to achieve some positive results of economic growth and development.
THE INFRASTRUCTURE AND ECONOMIC GROWTH AND DEVELOPMENT